Using Curriculum Mapping to Develop Undergraduate Nursing Informatics: A New Zealand Study - Collins, Emma; Britnell, Sally; Ditzel, Dr. Liz; Honey, Dr. Michelle (International Journal of Innovative Research in Medical Science, 2017)
Aim: The purpose of this research was to determine the range and scope of nursing informatics skills required by undergraduates. Methods: Curriculum mapping was used to assess the nursing informatics content of nursing curricula from three Schools of Nursing. Results: The mapping process showed where information communication technology skills were explicitly taught, those that students already knew, and identified gaps in student informatics learning and teaching delivery in the three undergraduate nursing programmes studied. Conclusion: These results make an important contribution to the nursing profession’s knowledge and understanding of nursing informatics teaching to undergraduate nursing students. Nurse educators need to be assured that the nursing informatics skills developed by students over the course of their undergraduate education will stand them in good stead for their future work as registered nurses.